Profitability and dividend policy: How does free cash flow explain this relationship? - Januarsi, Yeni; Sanusi, Fauji (Jurnal Siasat Bisnis, 2024)
Purpose – This study aims to examine the possible explanations for the inconsistency between profitability and dividend policy association. It also aims to carefully investigate the explanations of the free cash flow regarding the profitability-dividend policy relationship while specifying the shape of the moderating variables.Design/methodology/approach –This study uses LQ45-listed enterprises as research sample and adopt hierarchical moderating analysis as our methods. This study also uses 10-year observations from 2012-2020 with 170 firm-years observations represented by 17 companies.Findings – The results showed a positive association between profitability and dividend policy, suggesting that higher profit was capable of inducing firms to provide more dividend payments for the stockholders. Furthermore, increasing free cash flow strengthened the profitability-dividend policy relationship and it play a role as a pure moderator between both variables. Research limitations/implications – As this study use LQ45 sample firms, the interpretation from the research funding should be carefully made and generalizations should be done with caution. Also, current study does not include managerial characteristics as potential factors to influence dividend policy due to data limitation. Practical implications – This study provide implication for managers by suggesting that the free cash flow condition of a company may be essential for deciding dividend payout policy when firms can create good profitability. Firms need to maintain its fee cash flow level to gain benefit as a driver to create favorable dividend policy for stockholders. Originality/value – This study adds essential contribution to the moderating role literature by distinguishing the type of moderating role of free cash flow on the relationship between dividend policy and profitability. In addition, this study also incorporates hierarchy regression analysis which is different from prior similar study.